Photocatalytic degradation of disperse azo dyes in textile wastewater using green zinc oxide nanoparticles synthesized in plant extract: A critical review - Dihom, Hussin Ramadan; Al-Shaibani, Muhanna M.; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel Ali; Ajit Sharma, Ajit Sharma; Khamidun, Mohd Hairul (Elsevier, 2022)
Textile wastewater comprises a complex mixture of chemical substances and dyes such as disperse dyes which have a high potential as carcinogenic, mutagenic, and teratogenic. Textile wastewater effluent contributes 20% of the water pollution with a high contribution to environmental contamination, where about 50,000 tons/year of dyes are dumped into the environment. The advanced oxidation processes (AOPs), which includes photocatalytic degradation (PD) using nanophotocatalysts, is a rising technology causing in completing the mineralization of the dyes, compared to traditional treatment techniques such as the absorption method, which transfers the pollutants to other stages. Photolysis is capable of partially degrading 50 to 80% of micro-pollutants like dyes using nanophotocatalysts. The literature indicates that about 70 to 80% of studies use photocatalysis using ZnO/ TiO2 as a photocatalyst in wastewater treatment. However, the photocatalysts used have limited potential for removing dyes from textile wastewater. Thus, it is urgent to improve the ZnO NPs synthesis to maximize the PD efficiency to degrading textile wastewater dyes. The present review focuses on exploring the efficiency and mechanism of the photodegradation of textile wastewater dyes using zinc oxide nanoparticles (ZnO NPs) synthesized in the plant extract. The highest photolysis efficiency was found at low dye concentrations and pH to improve the initial operating parameters. Photolysis increases with increasing photocatalysis in the surface area and with an optimum amount of photocatalyst. Furthermore, appropriate photoirradiation is also necessary to conduct the photocatalytic process at room temperature.